Ir/TiONx/C high-performance oxygen evolution reaction nanocomposite electrocatalysts in acidic media: synthesis, characterization and electrochemical benchmarking protocol. (19th February 2020) - Loncar, Anja; Moriau, Leonard; Stojanovski, Kevin; Ruiz-Zepeda, Francisco; Jovanovic, Primoz; Bele, Marjan; Gaberscek, Miran; Hodnik, Nejc
Abstract: More efficient utilization of iridium is of immense importance for the future development of proton exchange membrane electrolyzers. In this study, we introduce a new facile and scalable synthesis of an Ir-based high-performance oxygen evolution reaction (OER) electrocatalytic nanocomposite. The composite consists of Ir nanoparticles with an average size of 3–4 nm, which are effectively anchored on a titanium oxynitride support (TiONx ), which is distributed across high-surface-area Ketjen Black carbon (Ir/TiONx /C). We provide complete structural, morphological and compositional characterization (x-ray diffraction, scanning transmission electron microscopy and energy-dispersive x-ray spectroscopy) and propose a proper benchmark protocol to measure true electrochemical performance. Compared to the state-of-the-art Ir Black electrocatalyst, Ir/TiONx /C exhibits approximately three times higher OER performance.